The Book of Jeremiah and What ‘Exile’ Means for the Hong Kong People in Diaspora Today - Wong, On Wing Tim (Asia journal of theology, 2024)
This paper examines the theological significance of the exile of Israel as depicted in the book of Jeremiah, with a special focus on chapter 29 and draws implications for the Hong Kong people who were forced to emigrate due to the social unrests in 2019 and the subsequent tightening policies implemented by the Beijing and Hong Kong governments. The experiences of the Babylonian exile resonate with the Hong Kong diaspora as they are similarly driven to depart from their native land and build new lives in foreign territories, despite differences in contexts and situations. By analyzing the biblical text and drawing parallels to the contemporary context, this study seeks to shed light on the theological implications of exile and offer insights that can be applied to the Hong Kong diaspora.